A viologen-based multifunctional Eu-MOF: photo/electro-modulated chromism and luminescence. Issue 86 (9th October 2020) - Fu, Ting; Wei, Yong-Li; Zhang, Chong; Li, Lin-Ke; Liu, Xiao-Fei; Li, Hai-Yang; Zang, Shuang-Quan
Abstract : A novel viologen-based multifunctional Eu-MOF integrating photochromism, photomodulated fluorescence, and electrochromic and electroluminochromic properties was investigated. Abstract : A novel viologen-based multifunctional Eu-MOF was obtained by integrating a luminescent component Eu(NO3 )3 ·6H2 O and a viologen-functionalized ligand. The Eu-MOF not only exhibited reversible photochromic and electrochromic properties, but also displayed photoluminescent and electroluminochromic properties.